Optimisasi Perencanaan Produksi RoPi (Roti Bikin Hepi) Menggunakan Linear Programming Metode Simpleks Pada Franchise RoPi Cabang Depok - Cibinong - Erlin Purwanti; Diah Pramestari (IKRAITH-Teknologi, 2022)
The general goal of a business in any field is to increase the number of customers.With an increase in the number of customers will increase profits because thedifference between business capital and operating results from the sale of productsor services is getting higher. The pandemic condition has resulted in a decline inpeople's ability to buy the products that are not their main needs. This decrease inpeople's ability resulted in a decrease in operating income which in the end theoperating profit per period also decreased. The decline in profits was also experienced at the Roti Bikin Hepi outlet which produces and sells coffee breadwith 3 flavors, those are original, chocolate and cheese. The number of unstablesales resulted in an increase and decrease in revenue at the Depok's Ropi outlets.Therefore, companies need to do better production planning to get optimal profits.The application of the Simplex method will be applied to solve problems at the Ropioutlet. Linear Programming will find the most optimal profit solution by taking intoaccount the constraints and in the form of linear inequality. Based on the results ofcalculations using the Linear Programming Simplex Method and the QM forWindows tool, it resulted that in order to get optimal profit the outlet must produceand sell 2,424 pcs of Original RoPi, 750 pcs of Chocolate RoPi, and 250 pcs ofCheese RoPi will get an increase in profit of Rp.10,731,800.